P105 Identification of 'large' alveolar macrophages and pulmonary intra-vascular macrophages in COPD patients. (12th November 2015) - Ravi, AK; Plumb, J; Mason, S; Booth, G; Vestbo, J; Singh, SD
Abstract : Background: A population of small macrophages with increased pro-inflammatory activity has been reported in COPD sputum. We have investigated macrophage size in the alveoli of COPD patients using immunofluorescence for the markers CX3CR1 and CD68. Methods: Formalin fixed paraffin embedded tissue blocks were obtained from an area of the lung as far distal to the tumour as possible from COPD patients, smokers (S) and healthy non-smokers (HNS) undergoing lung resection for lung carcinoma. Sections were labelled with an anti-CX3CR1 antibody and detected using an Alexafluor conjugated secondary antibody. Immunohistochemical detection of CD68 (enzymatic non-biotin amplification technique) confirmed the macrophage phenotype of CX3CR1+ cells. Results: All CX3CR1+ cells expressed CD68. The diameters of COPD macrophages were greater than controls (Table 1 ). Intravascular CX3CR1+CD68 + macrophages were observed in COPD and S (Table 1 ). Conclusion: Increased macrophage size in COPD may be linked to altered function. Pulmonary intravascular macrophages have been observed in other mammalian species and may promote pulmonary inflammation through direct release of cytokines into the pulmonary circulation.